OPTIMASI WAKTU EFEKTIF APLIKASI HERBISIDA PADA TANAMAN KELAPA SAWIT (ELAEIS GUINEENSIS JACQ.) DENGAN FUNGSI ESTIMASI DENSITAS KERNEL (Studi Kasus di Perkebunan Sawit PT SMART Tbk, Libo Estate, Riau) - Putri Aulia Wahyuningsih; Tatik Widiharih; Hasbi Yasin (Department of Statistics, Faculty of Science and Mathematics, Universitas Diponegoro, 2012)
Palm oil agribusiness is one of potential source to accelerate economic growth in Indonesia. Palm oil is the raw material to produce CPO (Crude Palm Oil) which is source of vegetable oil that is needed by all people. This research used a combination of 16 treatments of type and dose of herbicide on oil palm trees. Purposes of this research are to determine the optimal timing of herbicide applications and determine the treatment that maximizes efficacy of weed. Optimal timing of herbicide applications to the palm trees is determined through the largest mean of bootstrap resample and plot of kernel epanechnikov density estimation. Optimal treatment is determined through the largest mean of bootstrap resample, the smallest variance resample, the smallest range of bootstrap percentile confidency interval, and coverage probability that close to 1-α. Result obtained is the optimal timing of herbicide applications to oil palm trees is 8 weeks after applications. And optimal treatment is Tricalon 318 EC at a dose of 1500 cc.